Estimation of Congestion Cost of Private Passenger Car Users in Malioboro, Yogyakarta - Sugiyanto G.; Malkhamah S.; Munawar A.; Sutomo H. (Civil Engineering Dimension, 2010)
Congestion is the condition when the hourly traffic demand exceeds the maximum sustainable hourly throughout of the link. The aim of this research is to estimate the congestion cost of private passenger car users in central business district along the corridor of Malioboro, Yogyakarta, Indonesia. The amount of the congestion cost is the difference between perceived and actual generalized cost in traffic jam condition. In this paper, only the congestion costs of private passenger car users are estimated, as they are expected to shift to buses. The generalized costs from origin zone i to destination zone j consist of vehicle operating cost, travel time cost, and pollution cost. This study shows that while the perceived generalized cost for private cars at Central Business District (CBD) Malioboro is IDR 3101.00 per trip, the actual generalized cost in traffic jam condition is IDR 5802.00 per trip, giving the estimation of congestion cost in CBD Malioboro for private passenger car users as IDR 2701.00 per trip.